A Decision-Making Framework for Securing Compliant UCO Supply for SAF Production - Widodo, Ahmad Tiko; Novani, Santi (Dinasti Publisher, 2026)
PT Pertamina Patra Niaga (PPN) faces strategic challenges in sourcing qualified Used Cooking Oil (UCO) to meet Indonesia’s Sustainable Aviation Fuel (SAF) mandates. The government strictly enforces a 1% SAF blend by 2027 and 5% by 2029, pressuring PPN to secure a cost-effective and ISCC CORSIA-compliant supply chain. This study aims to evaluate four strategic alternatives: 100%